Legal Protection of Building Use Rights Over Land Management Rights in Batam City - Titik Aminah (Badan Penerbit STIEPARI Press, 2023)
Without legal clarity or certainty over the granting of new rights, the issue of legal protection for holders of Building Use Rights over Management Rights and the agreement’s contents is not a simple matter. This will impact the multiplication of legal vacancies governing the Right to Use the Building which is above the Land Management Rights. The aim to be achieved in this research is to find out the legal arrangements regarding the right to use the building above the land management rights in Batam and to find out the factors that constrain the implementation of the right to use the building over land management rights. The results showed that the application of building rights that were above the management rights resulted in a sense of injustice that resulted in the weaker community's right to prosperity and many factors that influence its application such as legal factors, factors of law enforcement officers, and the community. For this reason, it is hoped that more specific rules will be established regarding the authority to control land in Batam City and the need for socialization of the community related to the bureaucracy and the role of the Batam City Business Entity.